2005
DOI: 10.1001/archotol.131.10.900
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Mononucleosis and Corticosteroids

Abstract: Although many studies have examined the effects of systemic corticosteroid therapy (SCT) on the clinical course of infectious mononucleosis (IM), few have evaluated the influence of these studies on treatment patterns and outcomes. The purpose of this study was to review current therapeutic strategies and outcomes in uncomplicated and complicated IM. Design: Retrospective case series. Setting: Tertiary care center. Patients: We identified 206 immunocompetent patients with IM diagnosed during the previous 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 29 publications
1
23
0
6
Order By: Relevance
“…All cases included in this study had cervical lymphadenopathy; the posterior group was typically enlarged bilaterally in all cases associated with enlarged other neck nodes in 58.3% of cases and generalized lymphadenopathy in 41.6%. Thompson et al [15] described that the most common physical finding of IM patients was cervical lymphadenopathy as they detected it in 78.8% of their patients, Macsween et al [13] observed cervical lymphadenopathy in 88% while Grotto et al [12] observed it in 88.9% of their IM patients. Chan et al [11] described lymphadenopathy in 91% of their pediatric patients, while Krabbe et al [21] found lymphadenopathy in all children that proved to have IM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All cases included in this study had cervical lymphadenopathy; the posterior group was typically enlarged bilaterally in all cases associated with enlarged other neck nodes in 58.3% of cases and generalized lymphadenopathy in 41.6%. Thompson et al [15] described that the most common physical finding of IM patients was cervical lymphadenopathy as they detected it in 78.8% of their patients, Macsween et al [13] observed cervical lymphadenopathy in 88% while Grotto et al [12] observed it in 88.9% of their IM patients. Chan et al [11] described lymphadenopathy in 91% of their pediatric patients, while Krabbe et al [21] found lymphadenopathy in all children that proved to have IM.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid (monospot) tests for these heterophile antibodies are used to screen patients for infectious mononucleosis [14,15]. Heterophile antibody tests are negative in 25% of patients during the first week of infection and in 5-10% during or after the second week; once antibodies are present, they may persist for a year or more.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the medical records of Rochester Medical Center, Rochester, NY, found that nearly 45% of patients with infectious mononucleosis received systemic corticosteroids (200). Hence, the use of corticosteroids in infectious mononucleosis is a relatively common practice.…”
Section: Treatment Symptomatic Management Of Infectious Mononucleosismentioning
confidence: 99%
“…Otras indicaciones bien establecidas serían la anemia hemolítica o la trombopenia severas (5). Estudios recientes, sin embargo, demuestran que el uso de los corticosteroides en la práctica clí-nica es mucho más frecuente de lo esperado, no limitándose a las indicaciones antes comentadas y sin que por ello se objetive un aumento de las complicaciones (6). Probablemente, en este uso más liberal subyace la apreciación de un dramático alivio de los síntomas en los pacientes con MI que han recibido corticosteroides (7).…”
Section: Fig 1 Grandes Masas Quísticas (Flechas) De Contornos Mal Dunclassified